Personal Financial Management Skills Of University Students and Their Financial Experiences During The Covid-19 Pandemic - Lilian Gumbo; Mutengezanwa Margaret; Munyaradzi Chagwesha (Goodwood Publishing, 2022)
Purpose: The main purpose of this study was to assess university students’ financial management skills and their financial experiences during the Covid-19 pandemic. Research methodology: The research adopted the explanatory sequential mixed methods research design where a survey of 181 students on work-related learning was conducted using questionnaires and qualitative interviews. Data were analyzed using IBM SPSS Statistic 27 Results: The study established that the majority of the students do not have a budget, run out of money before receiving the next income, have no funds set aside for uncertainties or medical expenses related to the Covid-19 pandemic, and to make ends meet most of the students borrow money from relatives and friends. The majority of students struggled financially because of the Covid-19 pandemic. Limitations: Questionnaires and interviews were only distributed/conducted online due to the Covid-19 pandemic. Contribution: Personal financial management skills are a vital human capital skill for students. Therefore the need to explore such skills and financial experiences of University students during the Covid-19 pandemic for the first time.